Sistem Informasi Pembelian Dan Penjualan Obat Berbasis Web (Studi Kasus Klinik Putra Medika 4) - Bella Nandya Fahira (Prosiding Sains dan Teknologi, 2022)
Putra Medica Clinic is a Health Facility that servers treatment to be treatment of minor ailments. In addition to providing care and treatment, Putra Medika Clinic also provides various medicines that are tailored to the patient and doctor’s prescription. In carrying out the activities of buying and selling transactions, Putra Medika Clinic still uses a simple and not integrated application so that in the transaction there are often errors that cause different in stock or inventory. To be able to increase efficiency and effectiveness in carrying out purchase and transactions, the author tries to design a Web-Based Drug Purchase and Sales Information System so as to facilitate the transaction process at Putra Medika Clinic. In the process of developing the system the author uses the Waterfall method and in the process of testing the system the author uses Black-Box Testing and White-Box Testing. From the results of the Black-Box Testing and White-Box Testing, the purchase transaction has been integrade with the receipt, and when the user enters the receipt data it will be automatically stored as stock. With this Web-Based Drug Purchase and Sales Information System, it is hoped that the process of buying and selling drugs, monitoring and evaluating and recording report at the Putra Medika Clinic will be easier, more accurate, effective, and efficient. Keywords: Clinic, Website, Waterfall, Black-Box Testing, White-Box Testing, Effective, and Efficient